Simulation and optimization of catalytic reactor performance in phthalic anhydride production plant - Au Yon, Wei Kiat (2024)
The correlation of the respective reactor operating conditions and catalyst activity profiles with the magnitude and location of the hot spot temperature is important to predict the catalyst life and hence scheduling reactor shutdown for maintenance or catalyst changes before it leads to product off-spec in terms of quality and quantity. The application of Aspen Plus in the reaction temperature hot spot temperature profile to evaluate the catalyst activity through the impact of catalyst’s deactivation to the reaction performance as well as to correlate the catalytic activity with the industrial phthalic anhydride catalytic reactor conditions, product yield and purity. Subsequently to identify the best operating parameters for maximum phthalic anhydride (PA) yield with desired phthalic anhydride purity in the catalytic reactor. The evaluation showed that higher Mixing Ratio (MR) will result in higher production. However, the yield will drop as the residence time becomes shorter for reaction. As the bottleneck is the hot spot temperature not exceeding 455 oC, the optimum operating condition: Year 1 MR=78g with salt temperature 355.5 oC ; Year 2 MR=95g with salt temperature 360 oC ; Year 3 MR=84g with salt temperature 365 oC.